A review of Australian Government funding of parenting intervention research. (18th April 2022) - Havighurst, Sophie S.; Chainey, Carys; Doyle, Frances L.; Higgins, Daryl J.; Mathews, Ben; Mazzucchelli, Trevor G.; Zimmer‐Gembeck, Melanie; Andriessen, Karl; Cobham, Vanessa E.; Cross, Donna; Dadds, Mark R.; Dawe, Sharon; et al.
Abstract: Objectives : Parenting is central to children's optimal development and accounts for a substantial proportion of the variance in child outcomes, including up to 40% of child mental health. Parenting is also one of the most modifiable, proximal, and direct factors for preventing and treating a range of children's problems and enhancing wellbeing. To determine the effectiveness of new approaches to parenting intervention, and to evaluate how to optimise reach and uptake, sufficient funding must be allocated for high quality research. Method : We reviewed funding awarded by the National Health and Medical Research Council (NHMRC) and Australian Research Council (ARC) for parenting intervention research during 2011–2020. Results : Parenting intervention research received 0.25% of the NHMRC and ARC research budgets. Conclusions : There is a substantial mismatch between the funding of parenting intervention research and the impact of improved parenting on short‐ and long‐term child outcomes. To rectify this, it is critical that Australian Government funding schemes include parenting interventions as priority areas for funding. Implications for public health : Changes in allocation of funding to parenting research will support the establishment of evidence for the effective development, implementation and dissemination of parenting interventions to maximise health outcomes for children and their families.